Facts on Women Workers of Minority Races - Women's Bureau (DOL), Washington, DC.; Women's Bureau (DOL), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This booklet on women workers of minority races includes all races in a minority other than white, Negroes constituting about 90 percent of all persons other than white in the United States; Spanish-speaking persons are included in the white population. The following topics are encompassed; labor force participation; unemployment; marital status; women as heads of families; working mothers; children of working mothers; education; employment status of dropouts; occupations; full-time and full-year workers; and, earnings. Tabulated statistics are provided for the following; percent of persons in labor force, by sex, race, and age, 1971; percent of women in labor force, by race and marital status, March 1971; work experience in 1970 of women family heads in poor families, by race; percent of mothers in labor force, by race, age of children, and marital status of mother, March 1971; number of own children of working mothers, by race, type of family, and age of children, March 1971; employment status of high school graduates not enrolled in college and dropouts aged 16 to 21 years, by sex and race, October 1970; median years of school completed by workers 18 years of age and older, by sex and race, March 1959 and 1971; major occupation groups of employed women, by race, 1960 and 1971; and, median wage and salary income in 1970, by race and sex. (RJ)
Availability: Superintendent of Documents, U. S. Government Printing Office, Washington, D. C. 20402 ($0.15).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Age Differences; Comparative Analysis; Dropout Characteristics; Employed Women; Employment Patterns; Heads of Households; Labor Force; Marital Status; Minority Groups; Occupational Surveys; Racial Differences; Sex Differences; Statistical Analysis; Wages